Progressive Tax Changes to Superannuation in a Lifecycle Framework - George Kudrna; Alan D. Woodland (Center for Economic Studies and ifo Institute (CESifo), 2015)
This paper provides a quantitative analysis of hypothetical replacements of existing tax arrangements applied to superannuation (Australia.s term for private pensions) with traditional EET and TEE regimes. These taxation regimes exempt pension fund earnings from any taxation and tax either benefits or contributions progressively as regular incomes. By contrast, superannuation taxation features concessional flat tax rates on contributions and fund earnings, with benefits being generally tax free. Using an overlapping-generations model calibrated for Australia, we find that these hypothetical superannuation tax reforms have positive implications for vertical equity, as indicated by larger relative welfare gains and income improvements experienced by lower income households. The simulation results also show positive long run effects of the reforms on domestic assets as well as reduced pension expenditures.
Keywords: H55; E21; C68; 330; compulsory saving; pension and tax reforms; dynamic OLG model